Pelatihan Manajemen Pemasaran untuk Peningkatan Kualitas Pelayanan dan Promosi pada Usaha Mikro Kecil dan Menengah - Baharsyah, Syamsudin; Nurhasan, Nurhasan; Hasanudin, Hasanudin (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The aim of holding marketing management training through improving the quality of service and promotion for Micro, Small and Medium Enterprises (MSMEs) in Bojongnangka Village is expected to provide new insights to stimulate motivation and creativity in marketing MSME products in Bojongnangkan Village through improving service quality and appropriate promotions. A good understanding of marketing management, apart from enabling MSME business actors to increase sales volume, can also expand their business so that they can absorb more workers and reduce the unemployment rate in Bojongnangka. Some of the problems faced by partners are that they do not understand marketing management and still have little understanding of promotions, resulting in limited products being marketed. The method applied is starting with a pre-test, then material presentation, question and answer discussion and evaluation with a post-test. This PkM activity was attended by 20 participants from MSMEs in Bojongnangka. Training material regarding Marketing management through improving service quality and targeted promotions with the aim of ensuring that the goods being marketed can be widely distributed and reach more consumers. Promotions in various media, providing free testers, giving coupons, cash back and attractive price packages. The result of this community service activity is that participants' insight increases and stimulates motivation to always think innovatively and creatively, so that sales turnover can be significantly increased, driven by appropriate promotions and improved service quality that encourages customer loyalty compared to before attending the training. It is hoped that activities like this will not stop here, but can be continued in the next period with various similar activities, in order to increase knowledge and expertise by attending other activities such as seminars, webinars, training and coaching regarding marketing management to stimulate creativity and motivation. and innovation, also increase the capabilities of MSME business actors so that they can increase income and expand their business networks.